PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA MANGGALA BEAUTY CLINIC DI KOTA BLORA - Dea Ananda; Ihwan Susila (JURNAL LENTERA BISNIS, 2024)
The purpose of this study was to analyze the effect of service quality on customer loyalty with customer satisfaction as an intervening variable at Manggala Beauty Clinic in Blora City. This research method is quantitative. The population in this study were all people or customers who had treated and used products from Manggala Beauty Clinic. The number of samples in this study were 160 respondents. The sampling technique is non-probability with purposive sampling. The data used in this study are primary data. The data collection method used in this research is through distributing questionnaires. The data analysis technique used in this research is descriptive analysis and Structural Equation Model (SEM) analysis with Smart Partial Least Square (PLS). The results of this study are that service quality has a positive impact on customer satisfaction. Service quality has a positive impact on customer loyalty. Customer satisfaction has a positive impact on customer loyalty. Customer satisfaction can partially mediate the relationship between service quality and customer loyalty. Keywords: Customer Satisfaction, Service Quality, Customer Loyalty